A Genomic View of the Sea Urchin Nervous System - Burke, RD (2006)
The sequencing of the Strongylocentrotus purpuratus genome provides a unique opportunity to investigate the function and evolution of neural genes. The neurobiology of sea urchins is of particular interest because they have a close phylogenetic relationship with chordates, yet a distinctive pentaradiate body plan and unusual neural organization. Orthologues of transcription factors that regulate neurogenesis in other animals have been identified and several are expressed in neurogenic domains before gastrulation indicating that they may operate near the top of a conserved neural gene regulatory network. A family of genes encoding voltage-gated ion channels is present but, surprisingly, genes encoding gap junction proteins (connexins and pannexins) appear to be absent. Genes required for synapse formation and function have been identified and genes for synthesis and transport of neurotransmitters are present. There is a large family of G-protein-coupled receptors, including 874 rhodopsin-type receptors, 28 metabotropic glutamate-like receptors and a remarkably expanded group of 161 secretin receptor-like proteins. Absence of cannabinoid, lysophospholipid and melanocortin receptors indicates that this group may be unique to chordates. There are at least 37 putative G-protein coupled peptide receptors and precursors for several neuropeptides and peptide hormones have been identified, including SALMFamides, NGFFFamide, a vasotocin-like peptide, glycoprotein hormones, and insulin/insulin-like growth factors. Identification of a neurotrophin-like gene and Trk receptor in sea urchin indicates that this neural signaling system is not unique to chordates. Several hundred chemoreceptor genes have been predicted using several approaches, a number similar to that for other animals. Intriguingly, genes encoding homologues of rhodopsin, Pax6 and several other key mammalian retinal transcription factors are expressed in tube feet, suggesting tube feet function as photosensory organs. Analysis of the sea urchin genome presents a unique perspective on the evolutionary history of deuterostome nervous systems and reveals new approaches to investigate the development and neurobiology of sea urchins.